(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article discusses the relationship of basic and fundamental aspects of the evolution of music and the epochal formations of scientific and technical progress. It shows a new perspective on the emergence and development of music ranging from the classical art of J.S. Bach, G.F. Handel, Ch.W. Gluck, F.J. Haydn, W.A. Mozart, L. van Beethoven up to such musical constellations of contemporary classical music and creators of the new tonality and serial technique, such as A. Schönberg, O. Messiaen, K. Stockhausen, P. Boulez, L. Nono and E. Denisov. A unique analogy of music and science has been established in this article. Epoch-creating discoveries of the 20th century, such as the Structure of the Atom, the Theory of Relativity, Quantum Mechanics, etc., which radically changed our perception of the world, reflected in the development of music. If J. S. Bach – is the I. Newton of music, K. Stockhausen – is A. Einstein. The phenomenon of music – by no means a chance circumstances, but a manifestation of regularity. It is also a precious and spiritualizing fruit of human expanding horizons and worldview. It is shown that the art of music has evolved, and the phenomenon of music itself remains covariant. Key words: polyphony, sonata, tonality, dialectic, the diffusion of cultures, theory of relativity, quantum mechanics, dodecaphony (twelve-tone system), serialism, space and time.